Storage Duration and Red Blood Cell-Derived Microparticles in Packed Red Blood Cells Obtained from Donors with Thalassemia - Egarit Noulsri (2022)
Objective: To address the effects of storage duration on red blood cell (RBC)-derived microparticles (RMPs) in packed RBCs from donors who have thalassemia. Materials and Methods: Packed RBCs were prepared according to laboratory routine. The quantity of RMPs was determined using FACSCalibur and counting beads. Results: Across durations of storage, the packed RBCs from donors with thalassemia (n = 28) and healthy volunteers (n = 104) showed average RMPs to be 47,426 (10,139 127,785) particles/μL vs 49,021 (13,033 126,749) particles/μL, respectively (P =. 63). The peak RMP levels in donors with thalassemia and healthy volunteers, respectively, were shown in products from storage days 34 and 38. Both groups showed a trend toward a positive association between RMP concentration and the duration of storage in packed RBC bags stored under blood bank conditions. Conclusion: Our results suggest that storage-induced RMP release has similar effects in stored packed RBCs obtained from both donors with thalassemia and healthy volunteers.